The resistance in Western Europe 1940-1945 - Wieviorka, Olivier, 1960- (European perspectives., 2019)
"The resistance in Western Europe has long been considered a national phenomenon that provided a significant contribution, both politically and militarily, to Nazi defeat in World War II. But the so-called 'army of shadows' could never have risen without the support of London, first, and then of Washington. National factors thus played a preeminent part in the birth of the Resistance, while the British and Americans determined its growth. In A History of the Resistance in Western Europe, 1940-1945, Olivier Wieviorka provides a trans-European history of the resistance--analyzing the actions of clandestine resistance forces in Norway, Denmark, the Netherlands, Belgium, France, and Italy between 1940-1945, and figuring the role of the 'shadow soldiers' into the grand scheme of Anglo-American military strategy. Wieviorka illuminates the policies of governments in exile and the importance of finance, logistics, and British and American planning in defeating the Nazis. Drawing on archival documents and sources in English, Italian and Belgian, this account offers a welcome re-analysis of the place and role of national resistance movements--both unique in their own respect and their coordination when banded together."--Provided by publisher